The new world of RNAs - Dogini,Danyella Barbosa (2014)
One of the major developments that resulted from the human genome sequencing projects was a better understanding of the role of non-coding RNAs (ncRNAs). NcRNAs are divided into several different categories according to size and function; however, one shared feature is that they are not translated into proteins. In this review, we will discuss relevant aspects of ncRNAs, focusing on two main types: i) microRNAs, which negatively regulate gene expression either by translational repression or target mRNA degradation, and ii) small interfering RNAs (siRNAs), which are involved in the biological process of RNA interference (RNAi). Our knowledge regarding these two types of ncRNAs has increased dramatically over the past decade, and they have a great potential to become therapeutic alternatives for a variety of human conditions.